A field-enriched finite element method for simulating the failure process of rocks with different defects. (1st July 2021) - Wang, Long-Fei; Zhou, Xiao-Ping
Highlights: Field-enriched finite element method is proposed to simulate failure in rocks. This proposed method can select the appropriate failure criteria for voids and crack. Effectiveness and accuracy of proposed method are verified by numerical examples. The proposed method has a higher calculation accuracy and efficiency in some case. Abstract: A field-enriched finite element method is proposed in this paper to simulate the failure process of rocks. According to the different types of defects, the proposed method can select the appropriate failure criteria for voids and cracks. Field variables are used to characterize the crack location and to realize the influence of cracks on the physical field of the numerical model. The main features and the capability of the field-enriched finite element method to efficiently simulate the failure process of rocks with different defects are illustrated with some numerical examples. The results show that the field-enriched finite element method proposed in this paper can obtain the crack propagation path which is consistent with other numerical methods and experimental observations. Moreover, the numerical method proposed in this paper has the advantages of simple implementation process and higher computational efficiency and accuracy in some cases. Therefore, it is a promising numerical simulation method.